HFA of the ESC position paper on the management of LVAD‐supported patients for the non‐LVAD specialist healthcare provider Part 3: at the hospital and discharge. (28th September 2021) - Gustafsson, Finn; Ben Avraham, Binyamin; Chioncel, Ovidiu; Hasin, Tal; Grupper, Avishai; Shaul, Aviv; Nalbantgil, Sanemn; Hammer, Yoav; Mullens, Wilfried; Tops, Laurens F.; Elliston, Jeremy; Tsui, Steven; et al.
Abstract: The growing population of left ventricular assist device (LVAD)‐supported patients increases the probability of an LVAD‐ supported patient hospitalized in the internal or surgical wards with certain expected device related, and patient‐device interaction complication as well as with any other comorbidities requiring hospitalization. In this third part of the trilogy on the management of LVAD‐supported patients for the non‐LVAD specialist healthcare provider, definitions and structured approach to the hospitalized LVAD‐supported patient are presented including blood pressure assessment, medical therapy of the LVAD supported patient, and challenges related to anaesthesia and non‐cardiac surgical interventions. Finally, important aspects to consider when discharging an LVAD patient home and palliative and end‐of‐life approaches are described.